Clean and Green – The Volkswagen Emissions Scandal: Failure of Corporate Governance? - Poier, Stefan (Problemy Ekorozwoju, 2020)
In 2014, a scandal involving fraud and power shook the Volkswagen Group with far-reaching consequences that are yet to be fully revealed. This article examines the Volkswagen emissions scandal in terms of corporate governance failure. After a chronological review of the events that led to this extraordinarily damaging revelation, the main differences between the American and the German board system are described. Although Germany’s two-tier board is often considered superior to the American board system, weaknesses in the area of corporate ethics and culture that led to the crisis in the Volkswagen case are identified. The particular constellation within the Volkswagen group and its ownership structure reveals failures in management ethics that led to a certain kind of behaviour among employees that was not explicitly mandated by the management but was, nevertheless, in its interest in regard to achieving company goals.